De Novo nuclear genome assembly and annotation of Aizoon canariense L. (Aizoaceae): Uncovering genomic adaptations of a medicinal herb to arid environments (Bangladesh Journal of Plant Taxonomy, 2025)
In this investigation, whole genome sequencing and assembly of medicinally important species Aizoon canariense L. were performed to unveil its nuclear genome. The assembled nuclear genome length was 661.14 Mb, with an N50 value of 25,334 bp. The genome was largely homozygous, with a low level of heterozygosity ranging from 0.077 to 0.078%. BUSCO assessment exhibited 91.8% completeness based on the Viridiplantae database. Orthologous gene-based analysis revealed that the highest number of genes were associated with replication, recombination, and repair category. Gene Ontology (GO)-based annotation identified 5,814 genes involved in biological processes (BP), 25,137 genes linked to cellular components (CC), and 16,644 genes associated with molecular functions (MF). Pathway enrichment analysis identified the protein modification pathway representing the highest number of genes (807), whereas the pigment biosynthesis pathway exhibiting the lowest number of genes (75). A total of 20,448 repeat elements across 57 distinct types were identified in the assembled genome, with LTR/Gypsy being the most abundant, comprising 7,532 copies and spanning approximately 27,750 bp. These findings lay a strong foundation for future research on the molecular mechanisms of stress resilience in arid ecosystems targeting A. canariense.Bangladesh J. Plant Taxon. 32(1): 1-16, 2025 (June)